2021
DOI: 10.2147/ijgm.s336805
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress (Malondialdehyde) in Adults Beta-Thalassemia Major and Intermedia: Comparison Between Before and After Blood Transfusion and Its Correlation with Iron Overload

Abstract: Background: Iron overload is a major problem in both transfusion-dependent (TDT) and non-transfusion-dependent thalassemia (NTDT). It has been known to increase oxidative stress. Meanwhile, blood transfusion as main therapy for thalassemia increases iron overload. One of the markers of oxidative stress is malondialdehyde (MDA). This study aims to provide data on MDA levels in adult thalassemia patients, and to compare the levels before and after transfusion in patients with TDT and NTDT. Methods: This is a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Maintenance of serum ferritin below 1000 μg/L has been associated with improved clinical outcomes among all patients [18]; LIC up to 7 mg/g dw generally has no apparent adverse effects, while sustained LIC above 15–20 mg/g dw is linked with worsening prognosis [19, 20] and abnormalities [21]. Thus, patients in ULYSSES seem to have rather adequately controlled iron levels, compared with other previously published observational studies [14–16, 22–31]. Several factors could contribute to the observed differences, including variability in patient populations, genetic background, regions and observation periods, which determine available resources and application of different treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of serum ferritin below 1000 μg/L has been associated with improved clinical outcomes among all patients [18]; LIC up to 7 mg/g dw generally has no apparent adverse effects, while sustained LIC above 15–20 mg/g dw is linked with worsening prognosis [19, 20] and abnormalities [21]. Thus, patients in ULYSSES seem to have rather adequately controlled iron levels, compared with other previously published observational studies [14–16, 22–31]. Several factors could contribute to the observed differences, including variability in patient populations, genetic background, regions and observation periods, which determine available resources and application of different treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Thalassemia is a genetic disease of abnormal hemoglobin moieties of red blood cells (RBCs) 1 , resulting of abnormal and unpaired α-globin chain, or by abnormal globin molecules synthesis leading to fragility of RBCs membrane, with subsequent easily broken down of erythrocytes, resulting in chronic hemolytic anaemia. [2][3][4] Moreover, the formed severe anaemia resulted in lifelong dependence on blood transfusions to sustain life 5 , a therapy that causes additional iron overload, with its complications and toxic effects. 6 Accumulation of iron lead to elevation of free toxic ferrous in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…7 Moreover, the accumulated ferrous form induces production of reactive oxygen species (ROS) including hydroxyl radicals (OH • ). [8][9][10] this dualistic impact of acculated unpaired globin chain and LPI facilitate the oxidant load on erythrocyte consequently reducing erythrocytes lifespan 11 increasing the chance of membrane lipid peroxidation 4 , increased lipid peroxidation processes with subsequent consumption of antioxidants. This consumption of antioxidants is responsible for constant intracellular oxidative stress, although oxidative stress is not the primary cause of thalassemia, it mediates several of its pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols can chelate iron ions or interfere with iron-related proteins (ferroportin (Fpn), hepcidin, ferritin, etc.) to participate in iron homeostasis, and multiple pathways have been reported that are involved in polyphenols-mediated bioactivities (Atmakusuma et al, 2021;Hatairaktham et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols can chelate iron ions or interfere with iron‐related proteins (ferroportin (Fpn), hepcidin, ferritin, etc.) to participate in iron homeostasis, and multiple pathways have been reported that are involved in polyphenols‐mediated bioactivities (Atmakusuma et al., 2021; Hatairaktham et al., 2021). Administrated via daily dietary supplementation, polyphenols offer more convenient and biosafe strategies for the prevention and medication of these diseases.…”
Section: Introductionmentioning
confidence: 99%